Human HA and polymerase subunit PB2 proteins confer transmission of an avian influenza virus through the air - Van Hoeven, Neal (National Academy of Sciences, 2009)
The influenza virus genes that confer efficient transmission of epidemic and pandemic strains in humans have not been identified. The rapid spread and severe disease caused by the 1918 influenza pandemic virus makes it an ideal virus to study the transmissibility of potentially pandemic influenza strains. Here, we used a series of human 1918-avian H1N1 influenza reassortant viruses to identify the genetic determinants that govern airborne transmission of avian influenza viruses. We have demonstrated that the 1918 HA gene was necessary for efficient direct contact transmission, but did not allow respiratory droplet transmission between ferrets of an avian influenza virus possessing an avian polymerase subunit PB2. The 1918 PB2 protein was found to be both necessary and sufficient for airborne transmission of a virus expressing the 1918 HA and neuraminidase. Also, it was found that influenza viruses that were able to transmit efficiently in ferrets were able to replicate efficiently at the lower temperature (33 °C) found in the environment of mammalian airway. These findings demonstrate that the adaptation of the HA and PB2 proteins are critical for the development of pandemic influenza strains from avian influenza viruses.